Multi-Drug Resistance of Bacterial Isolates among Dental Caries Patients - Yadav, K; Prakash, S; Yadav, NP; Sah, RS (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: Dental caries is a well known major oral health problem in most developing countries which has multifactorial etiology caused by many facultatively anaerobes. S. mutans is the main pathogen associated with this disease. Recently Multi-Drug Resistant (MDR) species of S. mutans were identified from the dental caries patients against many commercial antibiotics. MDR is a natural phenomenon, posing a serious worldwide threat to public health. Several therapeutic agents are available to treat or prevent tooth decay, but still global burden of the disease with MDR are emerging. Therefore, the present study was designed for assessing the antibiotic sensitivity pattern of commercially available antibiotics. Material and Methods: This cross-sectional study was carried out by following Standard protocols of Bergey’s Manual of Systematic Bacteriology to isolate and identify the organism and further followed by antibiotic susceptibility test of bacterial isolates by disc diffusion method. Results: Streptococcus mutans (40%) was the most predominant to cause dental caries followed by S. aureus with 28.92. Gram positive isolates were found to be frequently resistant towards penicillin and tetracycline whereas Gram negative isolates were found to be Cotrimoxazole resistant. Conclusion: A high frequency of penicillin resistance in oral isolates and its co-resistance to erythromycin, tetracycline, gentamycin and amipicillin among the pateints was observed. The various awareness programmes should be facilitating the appropriate use of antibiotic to re-establish dominance over diseases must be implemented. Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (1):37-44